State Darwin Museum Support Programs for Children with ASD and Developmental Disorders - T.S. Kubasova (Moscow State University of Psychology and Education, 2022)
ing the direction of creating and testing inclusive programs with the participation of visitors with autism spectrum disorders (ASD). Goals of inclusive programs and activities are expanding the sensory and emotional experience of children, broadening the horizons and research activity, improving the socio-cultural development and social adaptation. Among features of the programs are adapted classes; planning excursions for periods of the least number of visitors; development of programs with the account of sensory characteristics of children; interactive classes with tactile didactic material; use of social stories. Children and their families master natural science collections at the group and individual face-to-face work and online at adapted excursions and classes, master classes, quests and during the participation in the inclusive museum events. The results of the work carried out by the staff of the Darwin Museum with children with ASD are summarized in the results of the survey. Parents and teachers note an increase in the cognitive activity of children, their independence and creative initiative.